High-profit IPO strategies : finding breakout IPOs for investors and traders - Taulli, Tom, 1968- (Bloomberg financial series., 2013)
A detailed guide to the new era of IPO investing Typically generating a great deal of interest, excitement, and volatility, initial public offerings (IPOs) offer investors and traders with opportunities for both short-term and long-term profits. In the Third Edition of High-Profit IPO Strategies, IPO expert Tom Taulli explains all facets of IPO investing and trading, with a particular emphasis on the industries that are fueling the next generation of IPOs, from social networking and cloud computing to mobile technology. In the past year alone, many of these types of IP.